MAQASID AL-SYARI’AH ALA JASSER AUDA UPAYA MEREFORMASI HUKUM ISLAM MELALUI PENDEKATAN TEORI SISTEM - Lukman Hakim; Akhmad Rudi Maswanto (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2022)
Classical fiqh treasures that no longer adequately answer complex contemporary problems due to changes in the context of time, space, culture and contemporary science. It is necessary to reform efforts to the understanding and interpretation of Islamic law that is not only aimed at Fiqh but directed at the philosophy of Islamic law (Ushul Fiqh) which is the producer of fiqh laws. Among contemporary Muslim thinkers concerned with the reform of Islamic legal philosophy is Jasser Auda, who uses maqasid shari'ah as the base for rejecting his philosophy of thinking by using the system approach as a method of thinking and knife analysis. A new unthinkable approach to use in discussions and discussions on the philosophy of Islamic law and Ushul fiqh. Jasser Auda reformed Maqasid al-Syariah in a contemporary perspective from Maqasid al-Syariah which was once nuanced protection (Protection) and preservation (Preservation) to Maqasid al-Syariah which aspires to Development (Development) and breeding of Human Rights (human rights), even he suggested that the development of human resources (HR) become one of the main themes for public benefit today.